Krop, topografi og kulturelle transformationer – Dansk håndbold som case - Nielsen, Niels Kayser (Slagmark - Tidsskrift for idéhistorie, 2018)
This article deals with processes of cultural transformation in general and especially with the transformation from space to place; not only as a mental process but as a bodily practice as well. In this article team handball in Denmark is used as a case, not because of the use of the body as such in this sport, but in order to show that even in sport the body is not solely a body but a medium used as a way of appropriation of a space in order to make it a place. The main point is to show that the body is a crucial part of a cultural settlement in permanent transformation, where the question how to inhabit a place is important.